Intercultural Communication at Nurul Qur'an Islamic Boarding School, Cirebon Regency - Rosyidi, Imron; Khumaeroh, Kholidatul; Wahid, Arif Abdul (Gema Wiralodra, 2025)
Intercultural communication is a process of interaction involving individuals from different cultural backgrounds. In Indonesia, especially in Cirebon Regency, Islamic boarding schools have an important role in educating the younger generation, and are often a meeting place for various cultures from all over the country. This study aims to explore the dynamics of intercultural communication that occurs at the Nurul Qur'an Islamic Boarding School, located in Cirebon Regency. The research method used is a qualitative approach with a case study design. Data collection was carried out through in-depth interviews, participant observation, and documentation studies. The results of this study indicate that the Nurul Qur'an Islamic Boarding School is a space rich in cultural diversity, with students coming from various regions and different social backgrounds. Despite challenges in terms of language, social norms, and customs, this Islamic boarding school has succeeded in creating an inclusive atmosphere that supports intercultural interaction. Factors that influence intercultural communication in this Islamic boarding school include the role of caregivers in building tolerance values, multicultural education implemented in the curriculum, and active participation of students in joint social activities. The positive impact of this intercultural communication is reflected in the increased appreciation of differences, tolerance, and interpersonal skills among students.